Multistation observations of the azimuth, polarization, and frequency dependence of ELF/VLF waves generated by electrojet modulation. Issue 10 (7th October 2015) - Maxworth, A. S.; Gołkowski, M.; Cohen, M. B.; Moore, R. C.; Chorsi, H. T.; Gedney, S. D.; Jacobs, R.
Abstract: Modulated ionospheric heating experiments are performed with the High Frequency Active Auroral Research Program facility in Gakona, Alaska, for the purpose of generating extremely low frequency (ELF) and very low frequency (VLF) waves. Observations are made at three different azimuths from the heating facility and at distances from 37 km to 99 km. The polarization of the observed waves is analyzed in addition to amplitude as a function of modulation frequency and azimuth. Amplitude and eccentricity are observed to vary with both azimuth and distance from the heating facility. It is found that waves radiated at azimuths northwest of the facility are generated by a combination of modulated Hall and Pedersen currents, while waves observed at other azimuths are dominated by modulated Hall currents. We find no evidence for vertical currents contributing to ground observations of ELF/VLF waves. Observed amplitude peaks near multiples of 2 kHz are shown to result from vertical resonances in the Earth‐ionosphere waveguide, and variations of the frequency of these resonances can be used to determine the D region ionosphere electron density profile in the vicinity of the HF heater. Key Points: Collisional heating is the dominant process in D region electrojet modulation There is an azimuthal dependence to the HAARP‐induced ELF/VLF source Vertical resonances cause amplitude enhancements near multiple of 2 kHz